Thinking beyond success and failure: Dutch water expertise and friction in postcolonial Jakarta. (September 2020) - Colven, Emma
In 2014, a consortium of Dutch firms revealed the master plan for Jakarta's Great Garuda Sea Wall project, combining urban development and flood risk management. Though a ground-breaking ceremony was held, little progress has since been made, and the yet-to-be materialized project faces an uncertain future. Taking this project as its case study, this article examines the efforts of Dutch consultants to realize the proposed Great Garuda Sea Wall project in Jakarta, and the frictions encountered during this process. This article contributes to a growing scholarship in policy mobilities that interrogates instances of policy failure. I begin from the premise that there are valuable insights to be gleaned by examining projects and policies that occupy the space in between failure and success. By using the lens of friction, this article aims to think beyond these categories and their limitations. I demonstrate how friction can be simultaneously productive and disruptive to policymaking and mobilizing, therefore complicating binary representations of success and failure. Abandoning these limiting categories holds the possibility of enriching policy mobilities scholarship by opening up space for analyses of the messy and indeterminate processes that are central to policymaking, and which categories of success and failure are unable to capture. This is especially important for understanding policymaking in the context of the "global South" where projects often remain unrealized and such categories are less analytically useful.